(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Shepherd’s purse (Inonotus obliquus), popularly known as chaga, is a medicinal plant that grows on the bark of a birch tree. It is widespread in Eastern Europe, Russia, Korea, China and North America. Chaga, which has been used in traditional medicine since ancient times, is known for its rich composition and health benefits. The Shepherd’s purse plant protects the cells of the body from free radicals. Polysaccharides contained in the plant stimulate the body’s natural defense system. Some studies have shown that it has anti-tumor and anti-tumor effects. Helps reduce rheumatism, arthritis and other inflammatory diseases.